2017
DOI: 10.1016/j.ijbiomac.2017.03.099
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the fumarate hydratase repertoire in Trypanosoma cruzi

Abstract: Nifurtimox and benznidazole represent the only treatments options available targeting Chagas disease, the most important parasitic infection in the Americas. However, use of these is problematic as they are toxic and ineffective against the more severe stages of the disease. In this work, we used a multidisciplinary approach to characterise the fumarases from Trypanosoma cruzi, the causative agent of Chagas Disease. We showed this trypanosome expresses cytosolic and mitochondrial fumarases that via an iron-sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…This provides a framework for developing class I PfFH (and in general for class I FH) specific inhibitors that will have no effect on the human enzyme. A recent study has reported the inhibition of TcFH by DL-MSA with a K i value of 4.2 ± 0.5 µM while no effect was observed on the class II human FH (22). The reason for DL-MSA's high specificity for class I FH must stem from the presence of 4Fe-4S cluster that interacts with the C2-hydroxyl group of malate (11).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This provides a framework for developing class I PfFH (and in general for class I FH) specific inhibitors that will have no effect on the human enzyme. A recent study has reported the inhibition of TcFH by DL-MSA with a K i value of 4.2 ± 0.5 µM while no effect was observed on the class II human FH (22). The reason for DL-MSA's high specificity for class I FH must stem from the presence of 4Fe-4S cluster that interacts with the C2-hydroxyl group of malate (11).…”
Section: Discussionmentioning
confidence: 98%
“…The UV-visible spectrum with absorption maxima at 360 and 405 nm indicates the presence of 4Fe-4S cluster in the enzyme and 78 % reconstitution efficiency using an Ɛ value of 16,000 M -1 cm -1 at 410 nm (30). The addition of sodium dithionite lowered the absorption intensity at 405 nm indicating a reduction of the cluster (Fig 3b) (31)(32)(33)(34) (21) and Trypanosoma cruzi (22) while for those from bacteria and archaea, the values are in the micromolar range. The catalytic efficiency (k cat /K m ) of PfFH∆40 is similar to L. major FH but 10-100 fold lower than that reported for other class I FHs ( Table 2).…”
Section: Pffh Complements Fumarase Deficiency In E Coli-mentioning
confidence: 95%
“…Abundant interactions for ribosomal proteins might be suggestive of the rapid and extensive protein translation that accompanies parasite differentiation and multiplication following host-cell invasion [15]. The ironsulfur cluster fumarase activity has been shown to be essential for protozoan parasites such as Trypanossoma cruzi since its mitochondrial isoform is part of the tricarboxylic acid cycle and as such being central to aerobic respiration [28]. The TCP1 complex belongs to the HSP60 family protein that was detected in P.…”
Section: Discussionmentioning
confidence: 99%
“…Fumarases usually fall into two distinct classes according to their oligomeric state, sensitivity to oxygen and metal‐dependence . Class I fumarases are homodimeric (with a molecular weight of 120 kDa), contain an iron‐sulfur cluster (4Fe–4S) in the catalytic center and are oxygen‐sensitive . The class II fumarases are homotetrameric (with a molecular weight of about 200 kDa), are iron independent and carry no other cofactors .…”
Section: Introductionmentioning
confidence: 99%